Method construction of raft foundation / Mohammad Faqhrul Adzmi Khairuddin - Khairuddin, Mohammad Faqhrul Adzmi (Universiti Teknologi MARA, Perak, 2019)
Raft foundations are large concrete slabs that can support columns and walls. This raft foundation is spread under the whole building. This raft foundation is one of the substructures. This report conducted for the process to construct the raft foundation for cluster and semi detach house. The objective of this report is to discuss the process that is involved in constructing raft foundation and to identify the important problems facing during constructing the raft foundation. In this report it focuses on cluster and semi detach house raft foundation. The main thing for this report is the process involved in constructing raft foundation for the cluster and semi detach house.